Citra Perempuan Jawa dalam Novel Canting Karya Arswendo Atmowiloto dan Amba Karya Laksmi Pamuntjak - Maghfiroh, Nur Vitarini (ESTETIK : Jurnal Bahasa Indonesia, 2018)
This research describes: (1) the self image of Javanese women in Canting by Arswendo Atmowiloto and Amba by Laksmi Pamuntjak, (2) the role of Javanese women in domestic in Canting by Arswendo Atmowiloto and Amba by Laksmi Pamuntjak, and (3) the role of Javanese women in public in Canting by Arswendo Atmowiloto and Amba by Laksmi Pamuntjak. This research is qualitative research by using comparative literature studies which refers to content analysis method. Data in this research is get from dialogs and narrative from Canting by Arswendo Atmowilotoand Amba by Laksmi Pamuntjakin quotes. Based on the finding of research and discuss, it can be concluded as follows. Firsty, the self image of Javanese women is divided into two aspects, physical and psychological aspects. Secondly, there are three aspects of Javanese women’s role in domestic compared between Canting and Amba, decision-making in the family aspect, economic aspect and sexuality aspect. Thirdly, both of Canting and Amba describes the negative stereotypes that women are being seen as the second human being in the public sector and are not given the same right to education as men.